Integrating Lamongan Traditional Desserts into Culture-Based Instruction: A Culturally Responsive Pedagogical Approach to Enhance EFL University Students’ Critical Reading - Fatmawaty, Riryn; Retnaningdyah, Pratiwi; Mustofa, Ali (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
In English as a Foreign Language (EFL) instruction, culturally responsive pedagogy has drawn more attention recently, especially in settings where globalized curricula sometimes marginalize students’ cultural heritage. In order to improve university students’ critical reading abilities, this empirical study explores how incorporating culture-based training focused on traditional desserts from Lamongan, East Java, Indonesia, can function as a culturally responsive pedagogical strategy. The study, which involved 33 students from Universitas Islam Lamongan’s (UNISLA) English Education Department, used a classroom-based qualitative approach bolstered by reflective diaries, pre- and post-assessment, and classroom observation. After reading texts, narratives, and digital stories about Lamongan desserts including Wingko Babat, Es Siwalan, Es Bathil, and Jumbrek, the students were given critical reading assignments that emphasized moral principles, cultural symbolism, and interpretation. The results show that including local cultural elements greatly improved students’ critical awareness of text-context linkages, interpretative depth, and engagement. Following the intervention, students were more equipped to recognize latent moral meanings, bias, and cultural representation in reading passages. According to the thematic analysis, culture-based education fostered intercultural awareness and cultural pride while also fostering higher-order thinking abilities that were in line with Bloom’s taxonomy. Additionally, by encouraging empathy and respect for cultural variety both within and outside of the classroom, the method enhanced the affective component of learning. The study comes to the conclusion that EFL reading can be transformed from a tedious decoding assignment into a meaningful act of cultural inquiry and reflection through culturally grounded education based on local identity. It promotes greater integration of regional.